Evaluating the antimicrobial resistance patterns and molecular frequency of blaoxa-48 and blaGES-2 genes in Pseudomonas aeruginosa and Acinetobacter baumannii strains isolated from burn wound infection in Tehran, Iran. (September 2020) - Tarafdar, F.; Jafari, B.; Azimi, T.
Abstract: The aim of this study is to evaluate the antimicrobial resistance patterns and molecular frequency of bla GES-2 and bla oxa-48 genes in Pseudomonas aeruginosa and Acinetobacter baumannii strains isolated from burn wound infection in Tehran, Iran. In this study, 50 isolates of A. baumannii and 48 isolates of P. aeruginosa were collected from the Burn Unit of Shahid Motahari Hospital at Tehran, Iran. Antibiotic susceptibility tests of all isolates were carried out using the disc diffusion method, and the production of extended-spectrum β-lactamases (ESBLs) in isolates was surveyed by the double disc synergy method and based on CLSI (2019 AST M100) criteria. Finally, the frequency of bla GES-2 and bla oxa-48 genes was surveyed by PCR. Antibiotic susceptibility tests showed that 48/48 (100%) of P. aeruginosa isolates and 49/50 (98%) of A. baumannii isolates were resistant to ceftriaxone and cefotaxime, respectively. Ceftazidime exhibited the lowest (26/48; 54.1%) resistance rates against P. aeruginosa isolates. The production of ESBLs was seen in 8/48 (16.6%) and 3/50 (6%) of P. aeruginosa and A. baumannii isolates, respectively. On the basis of conventional PCR and sequencing, the frequencies of the bla GES-2 gene among P. aeruginosa and A. baumannii was 87.5% and 58%, respectively. Moreover, bla oxa-48 gene was detected in 70.83% and 92% of P. aeruginosa and A. baumannii isolates, respectively. Results suggest that antibiotic-resistant A. baumannii and P. aeruginosa strains isolated from burn patients are frequently found; therefore, it is absolutely necessary to implement continuous screening and follow-up programmes for detecting antimicrobial resistance.